PEMANFAATAN LIMBAH SERPIH BOR SEBAGAI MATERIAL PERKERASAN JALAN - Utamy S. Saputri; Paikun; Fitri Sondang (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2019)
Oil and Gas industrial activities (oil and gas) and mining, which is one of the stages of drilling activity, providing a sewage sludge causing environmental pollution in the area where they are carried. To overcome this, efforts should be made to minimize the impact on the handling of the environment. As one of the efforts is to use the material as a pavement coating products. This effort utilizing the former drilling mud that was as waste into something useful, as coating material pavement. The main raw materials used are waste flakes drill that resulted from the drilling of wells of a foreign company engaged in the geothermal field is located in the area of Salak Mount, Sukabumi - West Java. The composition of the material used is type I Portland cement, gravel, and shale drilling waste. Based on Government Regulation no. 18 1999 on Hazardous and Toxic Waste, sludge waste categorized B3 former rebels managed to do so in proving whether the waste contains a B3 or not. With workarounds or TCLP toxicity test. Prior to this research, drilling mud TCLP tested in Laboratory Center for Settlement of Bandung Regency in collaboration with the Laboratory of Physical Chemistry Department of Chemistry - Faculty of Science, University of Padjadjaran - Bandung. The test results are in the table shows that the drilling mud is still relatively far on the threshold of making it feasible and safe to use as intended.